2020
DOI: 10.1016/j.tmp.2020.100746
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the participants in creative tourism activities: Case studies from small and medium sized cities and rural areas from Continental Portugal

Abstract: Although cultural tourists increasingly seek to experience cultural events actively and to directly engage in creative activities, empirical knowledge about the creative tourist remains limited. This study aims to characterize the motivations and profile of creative tourists. The data was collected through a survey of participants in creative tourism activities in Portugal developed by 40 pilot institutions of the CREATOUR project during 2017 and 2018, with 814 usable questionnaires collected and validated. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 37 publications
3
28
1
3
Order By: Relevance
“…Conceptual development of the present study was supported by opinions of Paula Remoaldo, Jaime Serra, Noémi Marujo Juliana Alves, Alexandra Gonçalves, Sónia Cabeça, Nancy Duxbury, 2020, relating to study of reasons to visit natural territories including rural areas, 2020 [8].…”
Section: Methodsmentioning
confidence: 95%
“…Conceptual development of the present study was supported by opinions of Paula Remoaldo, Jaime Serra, Noémi Marujo Juliana Alves, Alexandra Gonçalves, Sónia Cabeça, Nancy Duxbury, 2020, relating to study of reasons to visit natural territories including rural areas, 2020 [8].…”
Section: Methodsmentioning
confidence: 95%
“…Grounded in approaches from previous investigations presented in the first section, and based on this case study, this article first explores the holistic experiences provided within the scope of creative tourism, considering the profile of creative tourists [36] according to the new research paradoxes of tourist demand suggested by some authors [27,33,40]. The Schmitt model of customer experience [41][42][43] was used as a basis to reflect on how holistic experiences were created to involve and engage tourists, and which adaptation strategies were established in the context of a pandemic.…”
Section: Methodsmentioning
confidence: 99%
“…Other authors suggested a development model towards sustainable and regenerative tourism by suggesting creative tourism activities, where they exerted the capacity of creative tourism to implement a "framework to develop innovative approaches for a sustainable cultural tourism that is place-responsive and communityengaged" [35] (p. 2) and which promotes a more balanced interest between locals and tourists. In addition to physical distancing requirements, the importance of the component of socialization and interaction of visitors with the local community are specific features of creative tourists [36]. In this vein, Kristina et al [37] call for tourism industry stakeholders to adopt adaptation strategies and maintain resilient behaviours in order to enhance and promote the continuity of travel consumption behaviours.…”
Section: Health and Safety In Creative Tourism Activities: Impacts Challenges And Strategiesmentioning
confidence: 99%
“…The experience of various countries demonstrates that young people and families with children are interested in domestic tourism in rural areas too (Celeste Eusébio, Maria João Carneiro, Elisabeth Kastenholz, Elisabete Figueiredo, DiogoSoares da Silva, 2017 [13]). In the present paper, studies of Paula Remoaldo, Jaime Serra, Noémi Marujo Juliana Alves, Alexandra Gonçalves, Sónia Cabeça, Nancy Duxbury, 2020, related to establishing the motives of visits to tourist destinations in rural areas, are taken into consideration [14].…”
Section: Background and Methodsmentioning
confidence: 99%